Cortisol awakening response in PTSD treatment: Predictor or mechanism of change. (August 2020) - Rauch, Sheila A.M.; King, Anthony; Kim, H. Myra; Powell, Corey; Rajaram, Nirmala; Venners, Margaret; Simon, Naomi M.; Hamner, Mark; Liberzon, Israel
Highlights: Male combat veterans with PTSD showed lower cortisol awakening response than combat controls at baseline. Higher PTSD severity was also related to lower cortisol awakening response. When controlling for PTSD severity, higher baseline cortisol awakening response was related to attenuated reduction in PTSD over treatment. Abstract: PTSD is associated with abnormalities in hypothalamic-pituitary-adrenal (HPA) axis activity. This includes enhanced HPA axis negative feedback, attenuated cortisol awakening response, and attenuated cortisol response to personal trauma script. Whether HPA axis function predicts treatment response or treatment related symptom reduction in PTSD remains unclear. In addition, the relative effects of different treatment modalities (i.e., medication and psychotherapy) on HPA axis is unclear. To address this gap in knowledge, the PROGrESS study examined cortisol awakening response across treatment in Veterans with chronic PTSD randomized to receive Prolonged Exposure + Placebo (PE + PLB), Sertraline + PE (SERT + PE) or Sertraline + Enhanced Medication Management (SERT + EMM). Salivary cortisol awakening response (CAR) was assessed at baseline, mid-treatment (week 6 and 12), post-treatment (week 24) and follow-up (week 36 and 52). Among males at baseline, combat veterans with PTSD showed lower CAR Area Under the Curve Increase (AUCi; M = 3.15, SD = 9.57) than Combat controls ( M = 7.63, SD = 9.07; p = .02), demonstrating combat veterans with PTSD have a less responsive system than combat controls. Higher PTSD severity was also related to lower CAR AUCi ( r = -0.52, p = .03). When controlling for PTSD severity, higher baseline CAR AUCi was related to attenuated reduction in PTSD and lower likelihood of high treatment response over treatment ( z = -2.06, p = .04).